The Effect of Transfer Funds and Intellectual Capital on Local Government Financial Sustainability - Hisyam Ichsan; Ahmad Mansur; Eni Novitasari (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to understand and assess the contribution of transfer funds and intellectual capital to the financial sustainability of local governments. Understanding more deeply how external factors such as fund transfers and internal factors that reflect intellectual capital affect the financial sustainability of local governments can help local governments optimize available resources and face various complex economic challenges in the future. This research method uses a quantitative research method with a correlational approach. Multiple Regression Analysis is the analysis method used to determine the impact of fund transfers and intellectual capital on local governments' financial sustainability. The link is expressed mathematically. The study's conclusions indicate that (1) fund transfers have a positive and significant impact on financial sustainability, and (2) intellectual capital has a positive and significant impact on financial sustainability.